FAKTOR RISIKO YANG BERKAITAN DENGAN KEJADIAN KANKER PAYUDARA DI RSUD PROF. DR MARGONO SOEKARJO PURWOKERTO - Jatmiko, Heli; Sekar Siwi, Adiratna; Apriliyani, Ita (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Breast cancer is a malignancy that originates from the glandular cells, glandular ducts and supporting tissues of the breast, excluding the skin of the breast. Cancer can start to grow in the mammary glands, milk ducts, fatty tissue or connective tissue in the breast. According to the Every year more than 185,000 women are diagnosed with breast cancer. There are risk factors for breast cancer, including age, family history, obesity, smoking and previous history of breast cancer. This type of research is descriptive analytic using case control design. The population in this study were breast cancer patients at Prof. Dr. Margono Soekarjo Purwokerto Hospital in June–August 2023 which recorded 101 patients diagnosed with breast cancer. The sample in this study amounted to 50 in the case group and 50 samples in the control group with a total of 100 samples. Data analysis in this study was univariate and bivariate performed by calculating the magnitude of risk factors (Odd Ratio / OR). The results showed that age is a risk factor for breast cancer (OR 6.7), family history is a risk factor for breast cancer (OR 1.5), obesity is a risk factor for breast cancer (OR 6.6), smoking is not a risk factor for breast cancer (OR 1) and a previous history of breast cancer is a risk factor for breast cancer (OR 12.3).